Graz, Originalsammlung des Instituts für Archäologie der Karl-Franzens-Universität - Karl, Stephan (2014)
The volume contains 93 objects originating from workshops of the East Greek Area, the island of Cyprus, the Greek homeland and the Western Mediterranean like South Italy or Etruria.The pieces are shown to a large extent for the first time. Among the geometric pottery a fragment of a monumental crater of the Dipylon workshop is particularly noteworthy, among the Corinthian pottery two large alabastra of the Luxus-group emerge, but the Attic red-figure style is represented as the most prominent by a hydria of the Berlin painter.